Dilema Pidana Mati Bersyarat Antara Kepastian Hukum dan Fenomena Deret Tunggu Kematian - Lim, Arron Jonatan; Siregar, Elizabeth; Wahyudhi, Dheny (Faculty of Law, Universitas Jambi, 2026)
The enactment of Law Number 1 of 2023 concerning the Criminal Code marks a paradigm shift in Indonesia's sentencing system by introducing a conditional death penalty through a 10-year probationary period. This policy is intended as a middle ground between retributive and rehabilitative justice. However, this research argues that such judicial innovation triggers new legal problems due to the normative ambiguity in Article 100 of the Criminal Code, specifically regarding the criteria for